Characteristics of Chromite Deposits at North Kabaena District, Bombana Regency, Southeast Sulawesi Province, Indonesia - Hasria; Masri; Suryawan Asfar; Arisona; Ali Okto; La Ode Restele; La Ode Ngkoimani; Rika Yustika (UIR PRESS, 2021)
The study area is located in North Kabaena District, Bombana Regency, Southeast Sulawesi. This paper is aimed to describe characacristics of chromite deposits. This study is conducted in three stages, three stages including desk study, field work and laboratory analysis. Desk study mainly covers literature reviews. Field work includes mapping of surface geology and sampling of representative rocks types. Laboratory analysis includes the petrologic observation of handspecimen samples, petrographic analysis of the thin section and ore microscopy for polished section. The results of petrographic analysis show that olivine minerals are generally replaced by minerals orthopyroxene and has been alterated by lizardite type serpentine veins with a fractured structure. The mineral olivine is also replaced by the mineral chrysotile as a secondary mineral with a fibrous structure. Based on ore microscopy analysis show that chromite has generally experienced a lateritification process and has been replaced by magnetite, hematite and geotite minerals. Chromite has experience process of weathering and alteration from its source rock caused by tectonics that occurred in the study area. The results shows that the characteristics of chromite deposits in North Kabaena District Chromite deposits has generally encountered in peridotite rock which have a grain size of 0.3-20 cm. Furthermore, chromite deposits in the study area are also encountered in podiform deposits, distributed locally and shows podiform to tubular shape with the dimensions of 30-60cm.